Os efeitos da bandagem e do exercício na estabilidade do tornozelo em atletas - Danilo Augusto Rocha da Silva (2024)
The present study aimed to describe the effect of taping and the effect of exercise on ankle stability in athletes. A literature review was carried out, searching the PubMed database, during the month of May 2023, filtering studies from 2018 to 2023 in English and Portuguese. The inclusion criteria were: (1) studies that used amateur and professional athletes aged between 18 and 65 years, (2) controlled clinical trials, (3) studies that addressed Kinesiotaping, brace or ankle brace and/or proprioceptive training, balance training or stability training as interventions, (4) articles that addressed stability and brace interventions separately or in combination and (5) articles whose outcome included the incidence of sprain and/or ankle stability. The exclusion criteria were literature review studies, cross-sectional studies, case-control studies, cross-sectional studies and studies that included Paralympic athletes, children, adolescents or elderly people in the sample. Nine articles were selected to carry out this literature review. Of the nine studies found, eight used exercises as an intervention and all had positive results, four used taping as an intervention and three had positive results and two used taping and exercises in combination and all had a positive effect on ankle stability. Exercises provide, positive results on ankle stability, and better results when compared to just applying a bandage or kinesiotape. The bandage can be used as an auxiliary method for ankle stability.